Resisting linguistic imperialism in English teaching - Canagarajah, A. Suresh (Oxford : Oxford University Press, 1999)
"This book describes the creative strategies employed by teachers and students in periphery communities to use the English language in a manner that suits their needs and aspirations while subtly resisting the linguistic imperialism that many scholars have identified as the consequence of the global ELT enterprise. After developing trends and ideas from these oppositional strategies, the book goes on to outline elements of critical pedagogy suitable for English Language Teaching in formerly colonized communities."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Sri Lanka; English language -- Study and teaching -- Social aspects -- Sri Lanka; English language -- Study and teaching -- Political aspects -- Sri Lanka; English language -- Study and teaching -- Foreign speakers